Factors Influencing Shared E-Bike Usage Intention among College Students in Chongqing: UTAUT-TAM Integration - Cheng, Chen; Thongma, Watcharanan; Inthurit, Danaikrit; Sitthikun, Suthira (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study focuses on students from 5 universities in Dazu District, Chongqing, aiming to explore their willingness to use shared electric bicycles and the influencing factors. It integrates the Diffusion of Innovations Theory, Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Theory of Planned Behavior as the analytical framework. An online questionnaire was used for data collection, and 391 valid samples were selected from students who have used shared electric bicycles. The research results show that there are differences in the acceptance factors of shared electric bicycles among students across different theoretical dimensions: in the diffusion of innovations dimension, the key acceptance factors are compatibility and trialability; in the technology acceptance and utilization dimension, performance expectancy and effort expectancy play prominent roles; in the planned behavior dimension, perceived behavioral control is the core influencing factor. Multiple regression analysis results indicate that the most significant factor affecting students’ willingness to use shared electric bicycles is perceived behavioral control (regression coefficient = 0.254), followed by performance expectancy (0.188), compatibility (0.165), trialability (0.124), and effort expectancy (0.113). The conclusions of this study can provide empirical references for operators of shared electric bicycles to optimize their service strategies in university areas, and also fill the research gap in the interdisciplinary field of "mountainous terrain, college student groups, and willingness to use shared electric bicycles".